Reno's Big Gamble : Image and Reputation in the Biggest Little City. - Barber, Alicia (Book collections on Project MUSE., 2008)
Chronicles the creation and transformation of Reno's reputation from backward railroad town to a nationally known ""Sin Central."" The author shows how Reno civic leaders, in their never-ending quest for tourist dollars, dramatically altered the economy and physical appearance of the city.